Karakter Perempuan Dalam Televisi (Analisis Resepsi Peran Istri Sebagai Tulang Punggung Keluarga Dalam Sitkom "Tetangga Masa Gitu" Di Net TV) - Prasetyo, Dian; , Rina Sari Kusuma, M.I.Kom (2017)
Media construction tends to show women's character that was complex and contradictory related with feminine and masculine. Negative stereotype of women's character is often showed in weak condition and always exploited by media as a complement object. Actually, women are not identical with inferior and men are superior, women also are not identical with domestic matter and men with public matter. Nevertheless, it cannot be denied that patriarchal system adhered the labeling of subordinated women. This study aimed to know how Indonesian created perception of womens character in television program by influencing the differences of gender, culture, an ethnic, and religion backgrounds. Research reception analysis was used to know the audiences role as active viewers in interpreting women's character that was showed according to their opinions. The researcher used descriptive qualitative method by implementing Focus Group Discussion (FGD) by dividing 3 small groups that was contained by 4 members in each group. The members of FGD contained of three groups, FGD A did the research at Surakarta City, and FGD B and C groups did the research at Semarang City. FGD members consist of sophomore, housewife, and carrier women. All of them consist of Java, Lampung, Jambi, and Kalimantan ethnics and Islam & Christian religions. The result of this study showed that the qualification was consist of an age, gender, status, culture, religion, and experience were influenced how they way they gave a meaning on a media construction relating with women's character which was showed. According to Focus Group A, the current media showed that women's character was equal with mens position. On the other hand, according to Focus Group B, in the comedy situation (Sitkom) Tetangga Masa Gitu was constructing the women's character was not suitable if it was linked with culture and religion in Indonesia. It was different with the previous research, according to Focus Group C chose to associate all of media construction with its experiences.